Search for Charged Higgs Bosons Decaying into Top and Bottom Quarks in pp Collisions - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Mundal, O.; et al. (Amer Physical Soc, 2009)
We describe a search for production of a charged Higgs boson, qq>-> H(+), reconstructed in the tb final state in the mass range 180 <= M(H)(+)<= 300 GeV. The search was undertaken at the Fermilab Tevatron collider with a center-of-mass energy s=1.96 TeV and uses 0.9 fb(-1) of data collected with the D0 detector. We find no evidence for charged Higgs boson production and set upper limits on the production cross section in the types I, II, and III two-Higgs-doublet models (2HDMs). An excluded region in the (M(H)(+), tan beta) plane for type I 2HDM is presented.